Seeing Domestic Violence in Gorontalo from the Point of View of Criminology - Ardi Rauf; Vifi Swarianata (Estudiante Law Journal, 2022)
The purpose of this study is to find out the factors that cause the emergence of domestic violence crimes in the Gorontalo porles hokum area and to find out the efforts of the police to minimize cases of domestic violence crimes in the jurisdiction of the Gorontalo police. The method used in the study is empirical research with qualitative data. Approach techniques carried out in this data collection include Literature Studies, Interviews, and Questionnaires. The results showed that the causal factors behind someone committing violence in the jurisdiction of the Gorontalo police, among them were infidelity, economic factors, patriarchal culture, drunkenness, and playing gambling. The role of polri in dealing with domestic violence is, among others: Preventively, polri is more inclined to mediate. And Repressively: The role of the National Police is repressive on its own by carrying out actions, including Investigation, investigation, and Protection. An update on this research is that the author relates the theory of Criminology and the theory of punishment in this topic of discussion.